IMPORTANCE OF MULTIMEDIA TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Zoyirova Sevinch Shahobiddinovna,; Gʻafurova Dilfuza Jabborovna, (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article is about the concept of multimedia and interactivity in teaching foreign languages, the importance of multimedia resources and technologies in the process of teaching foreign languages, and the role of multimedia technologies in pedagogy.